1996
DOI: 10.1021/la9508194
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometry and X-ray Reflectivity Studies on Monolayers of Phosphatidylethanolamine and Phosphatidylcholine in Contact with n-Dodecane, n-Hexadecane, and Bicyclohexyl

Abstract: Monolayers of the phospholipids 1,2-dipalmitoylphosphatidylethanolamine (DPPE) and 1,2-dipalmitoylphosphatidylcholine (DPPC) are studied at the water/air interface in contact with n-hexadecane, n-dodecane, and bicyclohexyl by null ellipsometry and X-ray reflectivity along the isotherms. From recent diffraction data we derive refractive indices nx and nz to calculate the thickness of the mixed films in the condensed phase by ellipsometry. The thickness is compared with the results from X-ray reflectivity meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
79
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 25 publications
16
79
0
Order By: Relevance
“…Yet, if that happened, the alkyl chain remained in the hydrophobic moiety of the monolayer, as measurements of DPPC monolayers in an air atmosphere saturated with alkane showed. [27][28] The changed head group size affected the inter-and intramolecular interactions and therefore the thermodynamics of the monolayer. After the radical attack, we observed a decrease of π c , suggesting decreased intermolecular repulsion.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…Yet, if that happened, the alkyl chain remained in the hydrophobic moiety of the monolayer, as measurements of DPPC monolayers in an air atmosphere saturated with alkane showed. [27][28] The changed head group size affected the inter-and intramolecular interactions and therefore the thermodynamics of the monolayer. After the radical attack, we observed a decrease of π c , suggesting decreased intermolecular repulsion.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…7 Thus, the samples with r < 0.5 were heated up to [35][36][37][38][39][40] C and the samples with r $ 0.5 above 65 C. After dispersion the samples were cooled to room temperature and stored at a constant temperature of 20 C. To perform measurements the emulsions had to be diluted with water by different factors depending on the method used. Observation of various oil droplets showed that the characteristics of such droplets has never changed by diluting with water by different dilution factors.…”
mentioning
confidence: 99%
“…This situation has been encountered and thoroughly described for lipids at the oil/water interface by ellipsometry and reflectivity in case of lipids where a bulky phosphtidylcholine head-group is involved. 39 According to Thoma and coworkers, even in the liquid condensed phase, linear matched oil penetration significantly increases the surface pressure. These mechanisms could probably be also the origin of the low surface tension observed for emulsions leading to their long term stability.…”
mentioning
confidence: 99%
“…46,47 Refractive index values were estimated from the optical properties of similar lipids under comparable conditions of molecular packing and phase state. 40,46,48 For our single-wavelength measurements, the ellipsometry equations do not allow an independent determination of both the optical function and the thickness of the lipid bilayer from the values of ellipsometric angles, ⌬ and ⌿.…”
Section: E Optical Models For the Determination Of Ellipsometric Thimentioning
confidence: 99%
“…In these measurements for bilayers supported on silica, however, the effects of optical anisotropy on thickness are estimated to be below 1%. If previous estimates 47 of n ʈ = ͑1.47, fluid; 1.51, gel͒ and n Ќ = ͑1.42, fluid; 1.57, gel͒ are used, in conjunction with rigorous anisotropic optical calculations, 49 comparable values are obtained with the averages we have used of n = ͑1.45, fluid; 1.53, gel͒. While the 0.01°accuracy in ⌬ offers a substantial vertical resolution ͑Ͻ0.02 nm͒, the approximation engendered in our model and sample to sample variabilities limit the accuracy of absolute measurements to ϳ0.1-0.2 nm.…”
Section: E Optical Models For the Determination Of Ellipsometric Thimentioning
confidence: 99%